Analisis Kewenangan Kepala Daerah Dalam Menentukan Formasi Pengadaan dan Pengangkatan Pegawai Negeri Sipil - Wira Karnova Sandi; Irwandi Irwandi (Limbago: Journal of Constitutional Law, 2022)
Abstract This study aims 1) to determine and analyze the authority of regional heads in determining the formation of procurement and appointment of civil servants in the regions; 2) to find out and analyze the legal implications of regulations relating to the authority of the Regional Head (Governor, Regent/Mayor) in carrying out personnel management/ASN. The research method used is a normative juridical research type. The results of the study show that 1) Law Number 23 of 2014 concerning Regional Government, there are fundamental changes, especially those related to regional personnel management/administration, and apparently there is no single article that regulates the administration of personnel management affairs for civil servants. country in the area. In this regard, through Law Number 5 of 2014 concerning State Civil Apparatus, there are regulations relating to the authority of Regional Heads (Governor, Regent/Mayor) in carrying out personnel management/ ASN, which in its implementation is not further elaborated through Government Regulations. Number 11 of 2017 concerning the Management of Civil Servants; 2) legal implications for regulations relating to the authority of Regional Heads (Governor, Regent/Mayor) in conducting personnel management/ASN that the authority to determine the formation of Civil Servant procurement within the Regional Government is intended to address the problem so that there is no funding gap from the government to each region, because some of the funding for regional personnel (civil servants in the regions) comes from APBN revenues provided through the General Allocation Fund (DAU). Keywords: Authority, Regional Head, Procurement And Appointment Formation, Regional Civil Servants. Abstrak Penelitian ini bertujuan 1) untuk mengetahui dan menganalisis kewenangan kepala daerah dalam menentukan formasi pengadaan dan pengangkatan pegawai negeri sipil di daerah; 2) untuk mengetahui dan menganalisis implikasi hukum terhadap pengaturan yang berkaitan dengan kewenangan Kepala Daerah (Gubernur, Bupati/Walikota) dalam menyelenggarakan manajemen kepegawaian/ASN. Metode penelitian yang digunakan adalah tipe penelitian yuridis normatif. Hasil penelitian menunjukkan bahwa 1) Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan daerah, terdapat perubahan yang mendasar terutama yang berkaitan dengan manajemen/administrasi kepegawaian daerah, dan ternyata tidak ada satu pun pasal yang mengatur tentang penyelenggaraan urusan bidang manajemen kepegawaian bagi pegawai negeri sipil negara di daerah. Berkenaan dengan hal itu pula, melalui Undang-Undang Nomor 5 Tahun 2014 tentang Aparatur Sipil Negara, ada pengaturan yang berkaitan dengan kewenangan Kepala Daerah (Gubernur, Bupati/Walikota) dalam menyelenggarakan manajemen kepegawaian/ ASN, yang dalam implementasinya tidak dijabarkan lagi melalui Peraturan Pemerintah Nomor 11 Tahun 2017 Tentang Manajemen Pegawai Negeri Sipil; 2) implikasi hukum terhadap pengaturan yang berkaitan dengan kewenangan Kepala Daerah (Gubernur, Bupati/Walikota) dalam menyelenggarakan manajemen kepegawaian/ASN bahwa wewenang penetapan formasi pengadaan Pegawai Negeri Sipil yang berada pada Pemerintahan Daerah dimaksudkan adalah untuk mengatasi masalah agar tidak terjadi kesenjangan pendanaan dari pemerintah kepada masing-masing daerah, sebab sebagian pendanaan kepegawaian daerah (Pegawai negeri sipil di daerah) berasal dari pendapatan APBN yang diberikan melalui Dana Alokasi Umum (DAU). Kata kunci: Kewenangan, Kepala Daerah, Formasi Pengadaan Dan Pengangkatan, Pegawai Negeri Sipil di daerah.